Hijrah past and present - Ahmad, Khurshid; Cara, Anwar (Leicester : The Islamic Foundation, 1987)
The program talks about Hijrah which can be undertaken for security or economic reasons, the highest form consists of moving to a place where God's will can be fulfilled in all aspects of human existence. Hijrah is an essential part of Jihad and the enduring effort to create a society that conforms to the demands of faith, moral sublimity and sound equity
'Delivered at the FOSIS Summer Camp, July 1987, Liverpool'
Keywords: Muhammad, -- Prophet, -- d. 632 -- Hijrah